LEMAH SANAD BELUM TENTU LEMAH MATAN - Muammar, Arief (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2018)
This study discusses about the rule is not necessarily weak sanad weak matan hadith is a rule that applies only to the weak hadith. The rules of tradition of this kind can be used with the following conditions: first, the support strength of other traditions his matan matching, narrated of narrators (sanad path) to another, as well as the quality is equal or better than the first chain of transmission paths. Second, the narrators do not be evil, or a liar, nor a forger of hadith and is not known as one who fahusya gala?uhu (many false) and inattentive, not al-muttahim?na bil ka?ib (accused of lying), not heretical and not maj??l ?ain. Third, Hadith ?a??f not too weak as mursal hadith, mu?allal, and mubham. So the traditions are not too weak, they could still acceptable (maqb?l) if there is a path sanad from another hadith. Fourth, the hadith-hadith has a martyr and mut?bi?, meaning not only narrated the hadith with a chain of transmission lines, because it could conflict with the rules that have been understandable, as the hadith matr?k.